State of reconstruction of Ukrainian multifunctional stadiums after EURO-2012 - Chub, Oleksandr; Kreizer, Iryna (Linguistics and Culture Review, 2021)
Today, Ukraine, like the whole world, is going through difficult times, the state of the economy is affected by such problems as war, pandemics. However, even greater losses are caused by often ill-considered actions, there is no strategy for the development and planning of construction and reconstruction of existing multifunctional stadiums at both the regional and national levels. The article reviews the condition of several existing multifunctional stadiums inherited from Soviet times. The fate of these stadiums is different and similar at the same time. After holding the EURO-2012 football championship, years have passed and the authors of the article are interested in the question: has anything changed for the better in the field of design and reconstruction of multifunctional stadiums. The article considers both the newly made project according to modern requirements (“CSC ZSU” stadium in Kyiv), reconstructed for EURO-2012 (“Metallist” Stadium in Kharkiv), and the stadium that needs urgent action to implement the reconstruction project (“Metallurg” Stadium in Kryvyi Rih). An analysis of the results of the competition STEEL FREEDOM is also given as an example of a modern approach to the design of new modern stadiums.